Integrated thinking rolls! Stakeholder engagement actions translate integrated thinking into practice. Issue 4 (26th October 2020) - Devalle, Alain; Gromis di Trana, Melchior; Fiandrino, Simona; Vrontis, Demetris
Abstract : Purpose: This study aims to investigate the approaches to and the actions of integrated thinking (IT) based on stakeholder engagement practices to mitigate the perception of IT as an "abstract construct" and to overcome the "silos" thinking of managing, communicating and reporting. Design/methodology/approach: The research develops a single case-study of a leading Italian company in the sustainability setting: Lavazza. The authors gathered in-depth information with semi-structured interviews on their approaches to IT and actions of IT and the related stakeholder engagement practices which involved over time. Findings: This study addresses the concept of IT, arguing for integrated circularity as a strategic mindset, which builds upon open communication and collaborative partnerships with stakeholders for value creation. Research limitations/implications: The limitations of this study stem from the nature of a single case study, thus the findings are most relevant to those companies operating in comparable sectors with similar historical and organizational characteristics. Practical implications: The study provides a systematic framework of IT approaches and related actions based on stakeholder engagement practices that define a company as an integrated thinker. This can be used by managers and companies to implement an integrated logic of thinking and reporting. Originality/value: This is a pioneering study in this area as there are very few ones that take into account the relationship between the IT of design and reporting from a stakeholder perspective. The more IT is embedded in the business, the fuller the consideration of key stakeholders' interests is incorporated as a relevant part of conducting business.